2008
DOI: 10.1111/j.1365-2141.2008.07147.x
|View full text |Cite
|
Sign up to set email alerts
|

The addition of liposomal doxorubicin to bortezomib, thalidomide and dexamethasone significantly improves clinical outcome of advanced multiple myeloma

Abstract: SummaryRelapsed/refractory myeloma has a poor outcome because of multi-drug resistance, patient low-performance status and toxicity of conventional chemotherapy. To improve results, standard chemotherapeutics and drugs targeting the microenvironment are applied at the same time. Bortezomib, by inhibiting proteasome function, may enhance chemosensitivity to other drugs and overcome drug-resistance. Notably, doxorubicin and bortezomib may reciprocally increase their efficacy. Thus, to improve outcome whilst mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…However, cardiac toxicities have been observed in patients with chronic use of the proteasome inhibitor bortezomib (Velcade) (1,9,47). Nevertheless, chemotherapies combining Dox and proteasome inhibitors seem to show improved clinical outcome in clinical trials (6,46). Hence, it is hopeful that studies like the present one will stimulate very interesting and important investigations into whether chemotherapies combining Dox and proteasome inhibition display either less or more severe cardiotoxicity than those using either alone.…”
Section: Discussionmentioning
confidence: 81%
“…However, cardiac toxicities have been observed in patients with chronic use of the proteasome inhibitor bortezomib (Velcade) (1,9,47). Nevertheless, chemotherapies combining Dox and proteasome inhibitors seem to show improved clinical outcome in clinical trials (6,46). Hence, it is hopeful that studies like the present one will stimulate very interesting and important investigations into whether chemotherapies combining Dox and proteasome inhibition display either less or more severe cardiotoxicity than those using either alone.…”
Section: Discussionmentioning
confidence: 81%
“…Given the observed effectiveness and tolerability of lenalidomidebortezomib-dexamethasone, there is potential for further development of this 3-drug regimen, including the addition of a fourth agent, as has been investigated with combinations of bortezomib and thalidomide. [43][44][45][46][47] Reports from phase 2 studies of lenalidomidebortezomib-dexamethasone plus pegylated liposomal doxorubicin in frontline 11 and relapsed/refractory MM 48 have demonstrated the feasibility and activity of this 4-drug approach, although comparative studies are required to determine if efficacy is improved. Of interest in this context, frontline studies have suggested no additional benefit in adding cyclophosphamide to bortezomib, dexamethasone, and lenalidomide/thalidomide.…”
Section: Lenalidomide-bortezomib-dex In Rel/ref MM 1465mentioning
confidence: 99%
“…A phase III clinical study compared the efficacy of Neulasta injected as a single dose with that of filgrastin administered daily in patients with breast cancer. It showed a level of febrile neutropenia (FN) of 9-13% with Neulasta, lower than that of 13-20% observed 14 with filgrastin, (69). Other clinical studies confirmed the enhanced activity of Neulasta compared with filgrastin, (70), (table 2).…”
Section: Crlx-101mentioning
confidence: 82%
“…Myocet has also been tested for a combined treatment of MBC with docetaxel and trastuzumab (12) or with gemcitabine (13), as well as for treatments of relapsed/refractory myeloma (14), several different types of lymphoma (15,16,17) and sarcoma (18), (table 2). clinical efficacy of these treatments are publically available, (19).…”
Section: I1 Lipid Based Nanoformulationmentioning
confidence: 99%